2016
DOI: 10.1016/j.nicl.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Application of texture analysis to DAT SPECT imaging: Relationship to clinical assessments

Abstract: Dopamine transporter (DAT) SPECT imaging is increasingly utilized for diagnostic purposes in suspected Parkinsonian syndromes. We performed a cross-sectional study to investigate whether assessment of texture in DAT SPECT radiotracer uptake enables enhanced correlations with severity of motor and cognitive symptoms in Parkinson's disease (PD), with the long-term goal of enabling clinical utility of DAT SPECT imaging, beyond standard diagnostic tasks, to tracking of progression in PD. Quantitative analysis in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…For instance, Homogeneity_GLCM (Homogeneity2 in the present study) also presented small variability between different segmentation methods [23], was very robust with respect to delineation and PVC [24], and depicted good reproducibility on test-retest scans [19]. This also can explain the enhanced performance of such metrics in correlation with clinical measures [46]. We should also note that a given same name of a texture feature in different publications does not always correspond to the same definition [47].…”
Section: Discussionsupporting
confidence: 53%
“…For instance, Homogeneity_GLCM (Homogeneity2 in the present study) also presented small variability between different segmentation methods [23], was very robust with respect to delineation and PVC [24], and depicted good reproducibility on test-retest scans [19]. This also can explain the enhanced performance of such metrics in correlation with clinical measures [46]. We should also note that a given same name of a texture feature in different publications does not always correspond to the same definition [47].…”
Section: Discussionsupporting
confidence: 53%
“…Importantly, we saw that not using imaging information (features selected by NSGAII) can lower performance to around 4.48 (in prediction error) which was not statistically significantly than our 4.32 performance (see Supplementary materials, section III, Supplemental Table 1&2). In our other investigations we also found that conventional imaging measures do not correlate well with clinical measures (correlation coefficient = −0.008, p-value = 0.94) [29] nor improve prediction (9 ± 0.88) [20]. However, radiomics analysis of DAT SPECT images, going beyond conventional imaging measures, was seen to provide significant improvements (4.12 ± 0.43, p < 0.001) in both tasks.…”
Section: Discussionmentioning
confidence: 57%
“…Approaches based on machine learning aim to build classification or prediction algorithms automatically by capturing statistically robust patterns present in the analyzed data [26]. In our past efforts we used radiomic (texture) measures to show improved correlation with clinical measures [29] and, when combined with clinical measures, improved prediction of motor outcome (MDS_UPDRS III) [20]. Furthermore, our recent studies confirmed significant improvement of outcome prediction based on discovering of patterns in images using deep learning (see the Section 4) [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Several dozen studies investigating the clinical value of PET uptake heterogeneity (using TA or other methods) in various tumour types (including oesophageal, lung, rectal, breast, head and neck, and brain cancer, and lymphoma) as well as more recently in neurodegenerative diseases with PET [16, 43] and DAT SPECT [44] have been published in the last 4 years alone. More recently, a few studies have also focused on extracting features from both the PET and CT components (see the section Promising clinical results below).…”
Section: The Present: An Era Of Rapid Expansionmentioning
confidence: 99%